Intervención educativa farmacéutica para la prevención de diabetes mellitus tipo 2. centro poblado Ramón Castilla – Huanchaco - Trujillo - Cárdenas Sedano, Luz Nohely (2012)
Type 2 Diabetes Mellitus is a chronic and multiform, currently regarded as a public health problem, but at the same time the disease is largely preventable. For prevention of the disease have educational needs of communities, in order to keep them informed to control and prevent chronic diseases. To meet these needs was carried out The Pharmaceutical Education Intervention in the Centro Poblado "Ramón Castilla", District of Huanchaco, Province of Trujillo, La Libertad Department, The methodology was developed by educational talks about Type 2 Diabetes Mellitus, aimed at increasing the level of knowledge a sample of 40 participants, about risk factors, complications and treatment to promote the prevention of this disease; the data collection was performed by applying a test before (pre-test) and after (post-test) of the intervention. To determine the statistical differences between the two moments evaluative test was used t student (p <0.05). The level of initial knowledge was poor, with 0% excellent, 20% good, 18% regular, 63% low and then the intervention is increased to 48% excellent, 53% good and 0% regular and low. Finally, the Pharmaceutical Educational Intervention was able to increase the knowledge level of the population of type 2 diabetes mellitus that can prevent and detect this disease current prevalence